2006
DOI: 10.1111/j.1748-7692.2006.00081.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Age Structure and Productivity of Pacific Walruses Harvested in the Bering Strait Region of Alaska, 1952–2002

Abstract: Pacific walruses (Odobenus rosmarus divergens) are harvested by subsistence hunters in Alaska as they migrate north through the Bering Strait in the spring. Harvest records and biological specimens have been collected from the Bering Strait communities of Little Diomede, Gambell, and Savoonga since the 1950s. Harvest levels in the Bering Strait region peaked in the late 1980s and declined thereafter; however, there was considerable variation in the size and composition of the harvests among communities and ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 11 publications
2
40
0
Order By: Relevance
“…Some walrus harvest data show that the proportion of females in the catch has increased while the relative proportions of pregnant females have declined and the age of first reproduction has shifted. These changes are suggested to be related to harvest management regimes and changing environmental conditions resulting in a distributional shift for females and slower rates of growth, perhaps due to food limitations caused by a shift from a benthic to a pelagic-dominated system (Garlich-Miller et al 2006;Grebmeier et al 2010). Atlantic walruses might be somewhat more resilient to changes in sea ice because they utilize more near-shore areas for feeding (Born 2005), but all walruses are dependent on benthic-pelagic coupling permitting rich benthic communities of bivalves, which are fed in part by vertical flux from ice-algae and MIZ algal blooms (Hobson et al 1995;Grebmeier et al 2006a, b;Tamelander et al 2006).…”
Section: Arctic Marine Mammals and Their Association With Sea Icementioning
confidence: 97%
“…Some walrus harvest data show that the proportion of females in the catch has increased while the relative proportions of pregnant females have declined and the age of first reproduction has shifted. These changes are suggested to be related to harvest management regimes and changing environmental conditions resulting in a distributional shift for females and slower rates of growth, perhaps due to food limitations caused by a shift from a benthic to a pelagic-dominated system (Garlich-Miller et al 2006;Grebmeier et al 2010). Atlantic walruses might be somewhat more resilient to changes in sea ice because they utilize more near-shore areas for feeding (Born 2005), but all walruses are dependent on benthic-pelagic coupling permitting rich benthic communities of bivalves, which are fed in part by vertical flux from ice-algae and MIZ algal blooms (Hobson et al 1995;Grebmeier et al 2006a, b;Tamelander et al 2006).…”
Section: Arctic Marine Mammals and Their Association With Sea Icementioning
confidence: 97%
“…An analysis of fi ve decades (1950s-2000s) of walrus harvest records in the Bering Strait region, showed that the age at harvest for males and females increased and the pregnancy rate decreased over time (Garlich-Miller et al 2006 ). The age at fi rst , 1971-1978(Smith 1987 reproduction increased from 8 years in the 1950s and 1960s to 10 years in the late 1970s to early 1980s, suggesting that females were energetically stressed during the later period and the population overall was less productive.…”
Section: Changes In Life-history and Diet Of Walruses And Seals In Thmentioning
confidence: 99%
“…Past estimates of natural mortality were 1.5% annually (Fay et al, 1997), which based on a historical population estimate of approximately 250,000 walrus, represents about 3750 walrus, about half the range-wide harvests of 6000-9000 walrus in the mid 1980s (Fay et al, 1997). Current range-wide reported harvests have halved to 2400-4700 walrus since the 1990s (Garlich-Miller et al, 2006). In contrast, large-scale environmental changes are expected to increase natural mortality.…”
Section: Potential Biological Removal (Pbr) Approach To Marine Mammalmentioning
confidence: 96%
“…Fish and Wildlife Service, provides the most recent indications of change in age structure, productivity, and status of Pacific walrus. However, lack of data on walrus (e.g., recruitment rates or age/gender-specific survival), environmental health and conditions, biases in hunter preferences, and different harvest management regimes were acknowledged to limit conclusions about the relationship between life history parameters, population size, and the dynamic carrying capacity of the Beringian region (Garlich-Miller et al, 2006).…”
Section: Current Knowledge About the Size Of The Pacific Walrus Populmentioning
confidence: 99%